(untitled) (Altre Modernità, 2025)
The aim of this article is to show the narrative variations of two short stories by Silvana Grasso, “Manitta” (Pazza è la luna, 2007) and “Il cuore a destra” (2014), in the context of that “dimensione ‘silvanocentrica’ [fatta] più di autocannibalismo che di autocitazione” (Castiglione 2014). The comparative reading of the two texts demonstrates the circularity of themes and situations experienced by the two main characters in a game of reduplications and deviations that have the same origins, including the author’s own experience, and recur several years later in her production: both orphans and almost unschooled, brought up by their aunts, small and modest entrepreneurs, from whom they inherit the hated shops that they then transform into their own destiny, over which the shadows of death, of illness, of the violent sides of the immobile Sicilian province loom fiercely; both women exerting coercive power through an object with phallic valences, Angiolina’s fake hand and Billonia’s hairpin; both avoiding every social interaction, and who nevertheless pay dearly for the only exception. And if the birth defect will drag Angiolina down to hell, Apollonia will survive just thanks to that anomaly, her heart in the wrong place. Attention is also paid throughout this study to two other versions of the stories: “Angiolina la cappellaia” (1993) and the unpublished “Il cuore a destra” (2022), courtesy of the Archivio Silvana Grasso.